Refinancing behaviour by homeowners in Denmark when mortgage rates rise - Henrik Yde Andersen; Erik Grenestam; Marcus Bjerregaard Læssøe; Alexander Meldgaard Otte; Sigurd Anders Muus Steffensen (Danmarks Nationalbank, 2023)
Rising mortgage rates have led to one in five Danish fixed-rate mortgages to be refinanced during the first three quarters of 2022. The unique Danish match-funding principle has allowed fixed rate mortgage borrowers to buy back their existing mortgages at a 18 per cent discount, on average. 62 per cent of the realised net wealth gain has been used to reduce mortgage and bank debt, while 38 per cent was cashed out. The cash-out share is higher for borrowers with lower levels of wealth, indicating that cash outs may be used to support consumption now or as precautionary savings. Four in ten refinancers switched from fixed to adjustable-rate mortgages. When combined with cashing out, homeowners become more sensitive to adverse developments in interest rates and house prices. Nonetheless, most refinancers remain robust even in severe scenarios.
Keywords: 330; Hypothek; Hypothekenzins; Wohneigentum; Immobilienfinanzierung; Refinanzierung; Dänemark